Applications of structural health monitoring and field testing techniques to probabilistic based life-cycle evaluation of reinforced concrete bridges. - Colombo, Alberto Belotti (2016)
This work presents methodologies for the integration of field testing and Structural Health Monitoring SHM in the assessment of reinforced concrete bridges. The methodologies are demonstrated through the use of data collected during the testing of reinforced concrete railway bridges and long-term monitoring of a highway bridge. A probabilistic life-cycle prediction model based on sectional analysis is proposed for reinforced concrete structures. The updating of the model parameters is done using a Bayesian updating approach in which the problem is defined as a reliability one. An algorithm that uses subset simulation is used to sample points from the updated parameter distributions. Testing data from a reinforced concrete railway bridge is used to demonstrate the methodology and its results. The description of a SHM system that was installed in the Jaguari River Bridge is also presented. During the stages of preparation for the installation of this system the bridge was inspected, had NDT performed, and field testing was conducted using a test truck. The results of these tests are also presented. Analysis of the collected data from the live-load response of the Jaguari River Bridge is used to demonstrate methodologies for obtaining live-load response distributions from monitoring data. The use of this live-load response data is also used for the life-cycle analysis of one of the bridge\'s cross-sections.